Zoon's Balanitis: Benign or Premalignant Lesion? - Nicola Balato; Massimiliano Scalvenzi; Serena La Bella; Luisa Di Costanzo (Karger Publishers, 2009)
Zoon's balanitis or balanitis circumscripta plasmacellularis is a chronic disease of unknown origin.This condition usually manifests in middle-aged or elderly uncircumcised men. Although of unknown etiology, different factors have been reported to be involved in its genesis (local infections, poor hygiene, heat, friction, and constant rubbing). It is generally considered to be a benign condition, and its association with malignancies has been rarely reported. We report the case of an uncircumcised man, who developed clinically and histopathologically evident squamous cell carcinoma of the penis in an area affected by Zoon's balanitis.